Relationship building in L2 telecollaboration: examining language learner closings in online text-based chats. Issue 1 (2nd January 2019) - Kampen Robinson, Christine; Liebscher, Grit
ABSTRACT: Online exchanges among learners are an important form of communication in language learning contexts. This is due to the affordances this medium of communication creates for learning as well as the growing interest in internationalization of curricula. In fact, online communication can foster connections between people, including learners, across the globe. This paper is based on a qualitative analysis of online chat communication between Canadian learners of German and German learners of English. We discuss how these learners negotiate closing sequences in their chats, considering that the patterns for closing sequences may be different in different languages or be culture-specific and learners need to make choices on a spectrum between business focus (i.e. staying on task) vs. personal focus (i.e. addressing personal information). Hence, learners must negotiate interactive patterns that they may not be familiar with in creative ways that establish and maintain interpersonal relationships. Research about online communication helps to better understand learner communication, especially in an international context. In addition, it helps raise language awareness for teacher training and provides impetus for sensitizing teachers and learners to the ways in which interaction works and how relationships are maintained in communication.